2016
DOI: 10.1111/bdi.12400
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase‐3β in patients with bipolar I disorder: results from a prospective study

Abstract: The activity of GSK-3β is altered in euthymic bipolar disorder compared with healthy control subjects and varies with affective states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
1
5
0
1
Order By: Relevance
“…Observations in patients indirectly link the GSK3 β activity status with the bipolar phase cycling: a longitudinal study monitored at several time points the blood levels of inactivated GSK3 β, finding a correlation between higher inactivation and the predominance of depressive phases, as opposed to manic phases, where GSK3 β was mostly active. Interestingly, euthymic phases were associated with average levels of inactive-GSK3 β, that however were still lower than those observed in control subjects [70]. This observation is supported by other investigations, linking low activation levels of GSK3 β with depression phases of bipolar disorders, however low GSK3 β activity does not seem to be related with affective traits in healthy controls [71].…”
Section: Methodssupporting
confidence: 53%
“…Observations in patients indirectly link the GSK3 β activity status with the bipolar phase cycling: a longitudinal study monitored at several time points the blood levels of inactivated GSK3 β, finding a correlation between higher inactivation and the predominance of depressive phases, as opposed to manic phases, where GSK3 β was mostly active. Interestingly, euthymic phases were associated with average levels of inactive-GSK3 β, that however were still lower than those observed in control subjects [70]. This observation is supported by other investigations, linking low activation levels of GSK3 β with depression phases of bipolar disorders, however low GSK3 β activity does not seem to be related with affective traits in healthy controls [71].…”
Section: Methodssupporting
confidence: 53%
“…We have in two longitudinal studies with repeated assessments of patients with bipolar disorder during affective states (manic/mixed, depressive and euthymic) and healthy control individuals found that brain-derived neurotrophic factor (BDNF), 39 increased oxidative DNA and RNA damage 40 41 and decreased mRNA expression of the PTGDS gene encoding the prostaglandin D synthase enzyme 42 are markers related to the illness trait in bipolar disorder. The level of the cytokines IL-6 and IL-18 (interleukin) was related to manic episodes only and the activity of GSK-3beta varied with affective states, 43 suggesting that these may be state markers. 44 These results have contributed to the research area of biomarkers in bipolar disorder, moving the area closer towards identifying clinically applicable biomarkers.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Recently, a paper by Jacoby et al . titled ‘Glycogen synthase kinase‐3β in patients with bipolar I disorder–results from a prospective study’ was published in Bipolar Disorders .…”
mentioning
confidence: 99%
“…The strength of the study by Jacoby et al . is its prospective and longitudinal nature, with the authors obtaining samples from the same individuals at different time points.…”
mentioning
confidence: 99%